Match the following columns:
(a) ......
(b) ......
(c) ......
(d) ......
(a)
$\left((81)^{-2}\right)^{\frac{1}{4}}$
$=\left((9)^{-4}\right)^{\frac{1}{4}}=(9)^{-4 \times \frac{1}{4}}=(9)^{-1}$
$=\frac{1}{9}$
$=\frac{1}{9}$
(b)
$\left(\frac{a}{b}\right)^{x-2}=\left(\frac{b}{a}\right)^{x-4}$
$\Rightarrow\left(\frac{b}{a}\right)^{2-x}=\left(\frac{b}{a}\right)^{x-4}$
$\Rightarrow 2-x=x-4$
$\Rightarrow 2 x=6$
$\Rightarrow x=3$
(c)
$x=9+4 \sqrt{5}$
and
$\frac{1}{x}=\frac{1}{9+4 \sqrt{5}} \times \frac{9-4 \sqrt{5}}{9-4 \sqrt{5}}$
$=\frac{9-4 \sqrt{5}}{81-80}$
$=9-4 \sqrt{5}$
Now,
$x+\frac{1}{x}=9+4 \sqrt{5}+9-4 \sqrt{5}=18$
Thus, we have :
$x+\frac{1}{x}=18$
We know :
$\left(\sqrt{x}-\frac{1}{\sqrt{x}}\right)^{2}=x+\frac{1}{x}-2 \times x \times \frac{1}{x}$
$\Rightarrow\left(\sqrt{x}-\frac{1}{\sqrt{x}}\right)^{2}=18-2$
$\Rightarrow\left(\sqrt{x}-\frac{1}{\sqrt{x}}\right)^{2}=16$
Taking the square root of both sides, we get:
$\sqrt{x}-\frac{1}{\sqrt{x}}=4$
(d)
$\left(\frac{3}{2}\right)^{4 \times \frac{-3}{4}} \times\left(\frac{4}{3}\right)^{3 \times \frac{-1}{3}}$
$=\left(\frac{3}{2}\right)^{-3} \times\left(\frac{4}{3}\right)^{-1}$
$=\left(\frac{3}{2}\right)^{-3} \times \frac{3}{4}$
$=\left(\frac{3^{-3}}{2^{-3}}\right) \times \frac{3}{2^{2}}$
$=\left(\frac{3^{-3} \times 3}{2^{-3} \times 2^{2}}\right)$
$=\frac{3^{-2}}{2^{-1}}$
$=\frac{2}{9}$